Use of non-destructive testing for engineering critical assessment: Background to the advice given in BS 7910:2013. (January 2019) - Smith, A.T.; Schneider, C.R.A.; Bird, C.R.; Wall, M.
Abstract: BS 7910 contains guidance on the assessment of flaws in metallic materials. This paper outlines how and why the advice relating to non-destructive testing (NDT) has been expanded, and explains the scope and origin of the information, describing the key features of the new Annex T. Annex T gives tolerances which should be subtracted from the critical flaw size determined by engineering critical assessment (ECA) with the purpose of providing conservative, deterministic assessment of either the fitness for service of a known flaw or to provide a quantitative flaw sizing criteria for NDT. Advice is also provided for the size of flaw that can be expected to be detected with an acceptable probability of detection. The advice provided is generally suitable for butt welded ferrous plate with thickness of 10–25 mm, but in some cases has broader applicability. Advice is provided for the more commonly used methods of NDT. Highlights: Assessment to BS 7910 requires that flaws be detected, characterised and measured. BS 7910 Annex T provides advice on allowing for NDT uncertainties in the assessment. NDT capability is procedure-dependent and varies with the inspection situation. Inspection qualification may be needed to support safety-critical applications.